Barriers to, and triggers of, nurses' retirement saving: A decision-making approach - Tan, Louise; Tan, L (My University, 2014)
Australia, like many developed countries, places a strong emphasis on self-provision in later life. This is embodied in the Australian superannuation system, an earnings-related retirement savings mechanism. Women have been identified as a group poorly served by the existing retirement income framework and are more vulnerable to financial insecurity in old age. The implications of this for women’s retirement incomes provide the context in which this thesis is situated. There is a need for research that explores factors that affect individuals’ decisions to save for their retirement to inform and better target policy in Australia. This thesis aims to meet that need. Although there have been various explanations for women’s low retirement savings, not enough attention has been paid to the factors that influence the decision to save, especially for later life. This study uses a consumer decision-making framework that identifies a number of key stages in the decision-making process. This thesis argues that the decision-making process can be broken into two key stages: activities associated with making the decision to save for retirement; and the activities associated with actual savings behaviour. Using nurses as a case study and utilising a mixed methods approach, this study investigated nurses’ retirement planning behaviour and explored the factors that contributed to their success or failure in saving for their retirement. Information was collected primarily through semi-structured interviews. To complement the qualitative data, participants also undertook a self-completion survey that generated quantitative data about their financial preparation for retirement. Testing of early drafts resulted in moderate changes to the interview schedule, as well as the creation of the post-interview questionnaire. Further testing of the final interview schedule took place during the initial setting up/logistical phase of the project in April 2007. This included discussions with hospital administration, identifying locations for presentations, and so on. Testing resulted in very minor adjustments to the interview schedule that was used to guide the interviews used in this research. Fieldwork took place in South Australia, over a 10-week period between July and September 2007. A total of 37 nurses (of 156 nurses approached) were interviewed during this period, in both metropolitan and regional South Australia. All post-interview questionnaires were returned, resulting in a 100 per cent response rate. The findings outlined in this thesis were generated from the analysis of the primary interview and questionnaire data, as well as data from the retirement module of Wave 7 of the longitudinal panel survey, HILDA. HILDA data were used to support the results of primary data analysis or to identify any areas of difference. Within the HILDA sample (N= 13,327), it was possible to identify a nurse population (n=200). Whenever possible, this study highlights the responses of the nurse population separately to those of the general population. A typology was constructed and explained in this thesis to show that individuals can be classified into eight groups according to subjective and objective criteria based on retirement planning behaviour, as well as to the level of expressed concern about their financial future. Knowing the factors that influence the decision to save or purchase a financial product, along with the factors that sustain that decision and associated behaviour, could contribute to an individual’s success in being financially self-sufficient in retirement. This requires a clear understanding of the barriers to saving for retirement and, conversely, the factors that trigger individuals to adopt sustained savings behaviour. This study identifies a number of important barriers to, and triggers of, women’s retirement saving. Barriers included: poor financial literacy; limited information networks; the adverse influence of personal sources of information; and a lack of engagement with retirement. The milestone of reaching the age of 40 made individuals more aware and concerned about the imminence of their retirement, and emerged as a major trigger of active retirement saving amongst participants in this study. Other significant triggers were: family influence; changes in family structure—marriage, divorce and/or children; improved financial circumstances; and relocation. These are incorporated into an extended decision-making model that can be more readily adapted to long-term decision making. The findings of this study have significant analytical, practical and policy implications, especially for the increasing proportion of women who must rely on their own retirement savings rather than those of a partner or spouse. This research highlights current policies that affect financial security for women in retirement and identifies areas for reform.
Keywords: Gender -- Female; Ageing -- Superannuation usage and finance for aged care; Ageing -- Retirement; Gender; Ageing; Income, wealth and finances; Ageing; Gender; Female; Superannuation usage and finance for aged care; Retirement; Income, wealth and finance; Ageing; Gender